2017
DOI: 10.3892/ol.2017.6360
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β induces growth suppression in multiple myeloma MM.1S cells via E2F1

Abstract: Abstract. Transforming growth factor-β (TGF-β) has an important role in multiple target genes and signaling pathways. The E2F family of transcription factors is a group of DNA-binding proteins that are involved in cell-cycle progression, and therefore have a key role in proliferation. The present study demonstrates that inhibition of cell growth by TGF-β occurs in the multiple myeloma cell line MM.1S. However, the growth-suppressive effects of TGF-β may be reversed by small interfering (si)RNA to reduce the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In MM, tumor cells are confined to the bone marrow microenvironment, and are exposed to high levels of TGF-β secreted from both MM cells and bone marrow stromal cells, leading to further activation of cell growth and survival pathways [ 11 , 12 ]. Notably, it has been demonstrated that upregulation of SMAD1 and ID1 downstream of TGF-β signaling is indicative of activation of this pathway [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In MM, tumor cells are confined to the bone marrow microenvironment, and are exposed to high levels of TGF-β secreted from both MM cells and bone marrow stromal cells, leading to further activation of cell growth and survival pathways [ 11 , 12 ]. Notably, it has been demonstrated that upregulation of SMAD1 and ID1 downstream of TGF-β signaling is indicative of activation of this pathway [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, a study has indicated that cell proliferation was suppressed in TGF-b-treated MM.1S cells, which was reversed with anti-E2F1 siRNA treatment. 35 Collectively, this study indicates that suppressed lncRNA LUCAT1 blocked the activation of the TGF-b signaling pathway, thereby suppressing the growth of MM cells. In addition, lncRNA LUCAT1 might be a vital biomarker to assess prognosis in MM survivors.…”
Section: Discussionmentioning
confidence: 63%
“… 14 Furthermore, a study has indicated that cell proliferation was suppressed in TGF-β-treated MM.1S cells, which was reversed with anti-E2F1 siRNA treatment. 35 …”
Section: Discussionmentioning
confidence: 99%
“…The E2F family of transcription factors regulate cell function via gene transcription. E2F was reported as a novel fibrotic gene regulating pulmonary fibrosis ( 36 ). The enrichment of single gene GSEA in this study indicated that LPAR1 is significantly enriched in the “E2F target” pathway.…”
Section: Discussionmentioning
confidence: 99%